A prospective epidemiological survey of paediatric trauma in Africa: A cross-sectional study - Abdelbasit Elsayed Ali; Adesoji O Ademuyiwa; Kokila Lakhoo; John Kefas; Esperance Houmenou; Moruf Abdulsalam; Azakpa Leopold; Rouma Bankole; Seraphin Gbenou; Pautin Covi (Wolters Kluwer Medknow Publications, 2024)
Background: Trauma is a leading cause of morbidity and mortality in children worldwide. There is a need for development and provision of efficient paediatric trauma services based on adequate information and funding which are lacking in low- and middle-income countries. Aims: This study was carried out to assess the scale of the problem, identify the most common causes of trauma in Pan African Paediatric Surgical Association (PAPSA) zone and to define the limiting factors for provision of the necessary services required to reduce the potential mortality and disability. Materials and Methods: Data were collected through an electronic form sent out in PAPSA platform. Members were requested to provide prospective data on all paediatric major trauma admitted to or seen at their health facilities between the beginning of April 2019 and the end of June 2020. Hospital location, child's age, gender, type of injury, mechanism of injury, severity, initial management, method of transport, time to arrive to hospital, availability of surgical specialities, length of hospital stay and injury outcome were analysed. Results: There were 531 entries. The mean age was 3.53 years and median age 1.34 years. Male-to-female ratio was 2:1. The leading causes for injuries were falls 194 (36.53%) and motor vehicle crashes (MVCs) 176 (33.15%) followed by obstetrical 42 (7.9%), thermal 27 (5.1%) and domestic injuries 22 (4.1%). The most common injuries were limb fractures 181 (34.1%) and traumatic brain injury 111 (20.9%). Public and private transport were used in 313 (58.9%), while ambulance service was used in only 54 (10.1%). Distances to a health facility varied between 1 and 157 km. 70.2% of cases did not receive any primary care, while definitive care was received in 95.5% of the cases. Outcome was full recovery in 90.6% of patients, morbidity in 8.1% and a mortality rate of 1.3%. Conclusions: Most of the injuries were in the under 5-year age group. The two main causes of trauma in children in this study were the falls from height and MVCs. Long distance travels to reach health-care facilities were noticeable in this study, together with substantial lack of adequate ambulance facilities and shortage in necessary subspecialty services such as neurosurgical, orthopaedics and rehabilitation. Implementing proposed recommendations can reduce the burden.